2020
DOI: 10.1088/1478-3975/ab6819
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning- and pharmacophore-based prediction of RAGE inhibitors

Abstract: The receptor for advanced glycation end products (RAGE) has been identified as a therapeutic target in a host of pathological diseases, including Alzheimer's disease. RAGE is a target with no crystallographic data on inhibitors in complex with RAGE, multiple hypothesized binding modes, and small amounts of activity data. The main objective of this study was to demonstrate the efficacy of deep-learning (DL) techniques on small bioactivity datasets, and to identify candidate inhibitors of RAGE. We applied transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In our recent study [ 27 ], we attempted to compare the results of pharmacophore-based and ML-based drug design, and confirmed that results of pharmacophore-based and deep learning (DL)-based drug selection were similar in a significant part of the predicted drug candidates.…”
Section: Introductionmentioning
confidence: 78%
“…In our recent study [ 27 ], we attempted to compare the results of pharmacophore-based and ML-based drug design, and confirmed that results of pharmacophore-based and deep learning (DL)-based drug selection were similar in a significant part of the predicted drug candidates.…”
Section: Introductionmentioning
confidence: 78%
“…So we calculate the logarithmic values as eqs – for each, where the concentration unit of IC 50 , K d , and K i is nM. We regard a pair as positive when pIC 50 ≥ 6.0, or p K i ≥ 7.6, or p K d ≥ 7.0 normalp normalI normalC 50 = prefix− log ( I C 50 10 9 ) normalp K normali = prefix− log ( K i 10 9 ) normalp K normald = prefix− log ( K d 10 9 ) To demonstrate the effectiveness of our proposed model, we use the values of area under the receiver operating characteristic curve (AUROC), area under the precision-recall curve (AUPRC), accuracy, precision, and recall as evaluation metrics.…”
Section: Resultsmentioning
confidence: 99%
“…Some examples are represented by QSAR-ML models [40][41][42][43], multi-and combi-QSAR approaches [44][45][46][47][48][49][50]. Furthermore, in drug discovery field, advanced computational models, based on ML technology, hve demonstrated strong potential in selecting effective hit compounds [51][52][53][54][55][56][57][58]. Moreover, ML-based approaches represent a valuable resource also in drug repurposing field [59,60].…”
Section: Drug Discovery and Developmentmentioning
confidence: 99%